Ethics of a common good - Milan, Ornella; Bautista Silvestre, Juan; López, Tomas; Mercé, Agustina; Sousa Vinhote, Fabiana Viana; Chumpitaz, Analia; Stafolani, Claudio; Rateni, Liliana (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: wetlands are living systems and their integrity is key to the healthy life of this territory and those who inhabit it. The "echocide" for the constant burning of its grasslands and native flora, which not only sweeps the island vegetation and extinguishes species, but also alters the quality of the air we breathe and puts at risk the health of all the people we live in the region. Goals: describe the environmental and health problems, which is affected to the islanders, for the burning of wetlands, located in the Islands of Entre Ríos, in front of the Rosario Department. Methodology: we worked in El Espinillo, Marcos Sastre School No. 1139, School No. 45 Martín Jacobo Thompson. Encounters were held with islanders, about the problems generated by burnings in wetlands. Results: for the most part, the population mentioned that from the burns, the authorities prohibited the elimination of waste through incineration as they had been doing, without raising alternatives to this problem. There were a significant increase in eye symptoms. Another group of symptoms and signs of health conditions linked to smoke inhalation are: headaches, exhaustion. They also increased the transfer of animals (vipers, bats, rodents), to areas where people live. Conclusions: the destruction is not limited to fire, every day the irreparable damage to biodiversity, communities that inhabit and that depend on the wetlands for their subsistence are deepened. The legislative process of the Wetlands Law needs to move forward with the greatest possible speed, with commitment and political decision in support of the project agreed by the people through an open, transparent, collective, inter -institutional and multisectoral process promoted by the Commission of Natural Resources and conservation of the human environment.